Nano black phosphorus thick oil viscosity reducer as well as preparation method and application thereof

By combining the oil-soluble polymer-modified molybdenum disulfide nanosheets with black phosphorus nanosheets to form a nano-black phosphorus heavy oil viscosity reducing agent, the problem of complex synthesis and poor effect in the prior art is solved, and efficient reduction of heavy oil viscosity and good temperature and salt resistance are achieved.

CN119614175AActive Publication Date: 2025-03-14PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311177618.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-14
Estimated Expiration
2043-09-13

AI Technical Summary

Technical Problem

The existing oil-soluble heavy oil viscosity reducing agents are complex in the synthesis process and are easily affected by factors such as reservoir temperature and mineralization. The contact area between spherical nanoparticles and asphaltene is small, and the van der Waals force is weak in the molecule, which affects the effect of heavy oil viscosity reduction.

Method used

Molybdenum disulfide nanosheets modified with oil-soluble polymers are combined with black phosphorus nanosheets, and the modified molybdenum disulfide nanosheets are connected to the coupling agent of the black phosphorus nanosheets to form a nano-black phosphorus heavy oil viscosity reducing agent with strong polar groups, which enhances the action force with asphaltene.

Benefits of technology

It has achieved efficient reduction of heavy oil viscosity, with a viscosity reduction of up to 93.64%, and has the advantages of good temperature and salt resistance, good compatibility with crude oil, and difficult to accumulate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a nano black phosphorus thick oil viscosity reducer as well as a preparation method and application thereof. The nano black phosphorus thick oil viscosity reducer is prepared from the following raw materials: oil-soluble polymer modified molybdenum disulfide nanosheets, black phosphorus nanosheets and a coupling agent, wherein the mass ratio of the oil-soluble polymer modified molybdenum disulfide nanosheets to the black phosphorus nanosheets to the coupling agent is 1: 2: (2-6). The nano black phosphorus thick oil viscosity reducer has the advantages of strong acting force with asphaltene, high viscosity reduction rate, good temperature resistance and salt resistance, good compatibility with crude oil and difficult aggregation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum extraction, and particularly relates to a nano black phosphorus heavy oil viscosity reducer, a preparation method and application thereof. Background Art

[0002] Heavy oil accounts for more than half of the world's recoverable oil reserves. As the demand for oil resources in the global energy market gradually increases, the exploitation of heavy oil has received extensive attention from countries around the world. China's heavy oil classification standard defines heavy oil as having a viscosity greater than 50,000 mPa·s and a density greater than 0.98 g / cm 3 Crude oil with a viscosity of 10,000 to 50,000 mPa·s and a density greater than 0.95 g / cm 3 Crude oil is classified as extra heavy oil. Compared with ordinary heavy oil (viscosity less than 10000mPa·s), extra and extra heavy oil has higher colloid and asphalt content, greater viscosity and worse fluidity, which is not conducive to mining.

[0003] At present, the main methods for extracting heavy oil include thermal extraction, viscosity reduction by blending thin oil, and chemical viscosity reduction. Chemical viscosity reduction is considered to be the most promising method of extraction. This method is simple to operate, energy-saving and consumption-reducing, and is an important way to improve economic benefits. Chemical viscosity reducers are mainly divided into water-soluble viscosity reducers and oil-soluble viscosity reducers. Water-soluble viscosity reducers mainly disperse heavy oil into water-in-oil emulsions through emulsification, thereby reducing the viscosity of heavy oil, but there is a problem of difficulty in dehydration during post-processing. Oil-soluble viscosity reducers form hydrogen bonds between the strong polar functional groups on the viscosity reducer molecules and the colloidal asphaltene, disperse the asphaltene aggregates, and achieve the effect of reducing the viscosity of heavy oil. It is precisely because of the advantages that oil-soluble viscosity reducers can be directly mixed with crude oil, improve the fluidity of crude oil, and do not have post-processing problems that oil-soluble viscosity reducers have attracted people's attention.

[0004] Chen Ningning (Synthesis and performance study of a novel polymeric oil-soluble heavy oil viscosity reducer [J]. Chemical Reagents, 2017, 39(2): 4.) disclosed a quaternary copolymer oil-soluble polymer as a heavy oil viscosity reducer. The study showed that at 50°C, the viscosity reduction rate was 88.1% when 10% of the heavy oil viscosity reducer was added.

[0005] Chen Xiaokai (Synthesis and Performance Evaluation of Oil-soluble Viscosity Reducing Agent SA / MMA / VTEO Copolymer [J]. Chemical Engineer, 2016 (7): 5.) used three monomers, octadecyl acrylate, vinyl triethoxysilane, and methyl methacrylate, to carry out ternary copolymerization. The experimental results showed that at 50°C, the viscosity reduction rate could reach more than 80%.

[0006] With the widespread application of nanomaterials in the field of oil and gas field development, the research on the synthesis of heavy oil viscosity reducers using nanomaterials has attracted the attention of scientific researchers. Zhang Liquan (Indoor Research and Evaluation of Heavy Oil Nano Viscosity Reducers [J]. Chemistry and Bioengineering, 2022, 39(1): 52-54.) developed a water-based drilling fluid heavy oil nano viscosity reducer MLA with nanosilicon as the main agent. The viscosity reducer can reduce the viscosity of heavy oil emulsions. When the water content of heavy oil is 20%, the viscosity reduction rate at 75°C is as high as 60%.

[0007] The current oil-soluble heavy oil viscosity reducers are generally high molecular polymers, and their synthesis process is complex and easily affected by factors such as reservoir temperature and mineralization. In addition, the spherical nanoparticles have a small contact area with asphaltene and weak intermolecular van der Waals forces, which affect the effect of heavy oil viscosity reduction. The development of a new type of nano viscosity reducer for heavy oil, with a large contact area and strong interaction with asphaltene, is a practical problem that needs to be solved urgently. Summary of the invention

[0008] In view of the above problems, the present invention provides a nano black phosphorus heavy oil viscosity reducer, a preparation method and application thereof. The viscosity reducer has a strong interaction with asphaltene, good temperature and salt resistance, good compatibility with crude oil and is not easy to aggregate.

[0009] In one aspect of the present invention, a nano black phosphorus heavy oil viscosity reducer is provided, wherein the raw materials for preparing the nano black phosphorus heavy oil viscosity reducer include: oil-soluble polymer-modified molybdenum disulfide nanosheets, black phosphorus nanosheets and a coupling agent, wherein the mass ratio of the oil-soluble polymer-modified molybdenum disulfide nanosheets, the black phosphorus nanosheets and the coupling agent is 1:2:2-6.

[0010] As a specific embodiment of the present invention, the oil-soluble polymer-modified molybdenum disulfide nanosheets have a continuous phase containing an oil-soluble polymer and a dispersed phase containing molybdenum disulfide nanosheets dispersed in the continuous phase.

[0011] As a specific embodiment of the present invention, the polymer monomer of the oil-soluble polymer forming the continuous phase is selected from one or a combination of two or more of acrylamide, styrene, divinylbenzene, eicosyl methacrylate, docosyl methacrylate, and tetracosyl methacrylate; preferably, it is a combination of acrylamide, styrene, eicosyl methacrylate, and tetracosyl methacrylate; more preferably, the mass ratio of acrylamide, styrene, eicosyl methacrylate, and tetracosyl methacrylate is 2-3:7-8:42-43:48-49.

[0012] As a specific embodiment of the present invention, the molybdenum disulfide nanosheets forming the dispersed phase are selected from molybdenum disulfide nanosheets with a 1T crystal form, and the size of the molybdenum disulfide nanosheets is 100 to 200 nm.

[0013] As a specific embodiment of the present invention, the preparation method of oil-soluble polymer modified molybdenum disulfide nanosheets includes:

[0014] S1. Preparation of aqueous phase: mixing molybdenum disulfide powder with water and then performing ultrasonic stripping to obtain an aqueous phase;

[0015] S2, oil phase preparation: polymer monomers, oil-soluble emulsifiers, and oily solvents are mixed to obtain an oil phase;

[0016] S3, emulsification: adding the water phase to the oil phase and stirring to form a uniform and stable emulsion;

[0017] S4, polymerization: adding an initiator to the emulsion under an inert atmosphere and heating to cause a reaction;

[0018] Preferably, the ultrasonic time is 20 to 30 minutes, and the ultrasonic frequency is 40 KHZ;

[0019] Preferably, the mass ratio of molybdenum disulfide powder to polymer monomer is 1:100-400;

[0020] Preferably, the oil-soluble emulsifier is selected from one or a combination of two or more of dodecylphenol polyoxyethylene ether, sorbitan monostearate, sorbitan monopalmitate, and polysorbate 60; preferably, the amount of the oil-soluble emulsifier is 5 to 10% of the total volume of the emulsion raw material;

[0021] Preferably, the oily solvent comprises toluene;

[0022] Preferably, the initiator comprises azobisisobutyronitrile; preferably, the amount of the initiator is 0.6 to 1% of the mass of the polymer monomer;

[0023] Preferably, the reaction temperature is 50-90° C., and the reaction time is 4-8 h.

[0024] As a specific embodiment of the present invention, the size of the black phosphorus nanosheets is 50 to 100 nm.

[0025] As a specific embodiment of the present invention, the coupling agent is a silane coupling agent, which is selected from any one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

[0026] The second aspect of the present invention provides a method for preparing the aforementioned nano black phosphorus heavy oil viscosity reducer, comprising: mixing oil-soluble polymer-modified molybdenum disulfide nanosheets, black phosphorus nanosheets, a coupling agent and an oily solvent, and stirring to react; preferably, the oily solvent comprises toluene; preferably, the reaction temperature is 30 to 50°C, and the reaction time is 8 to 12 hours; preferably, the reaction product is washed and dried.

[0027] The third aspect of the present invention provides the use of the aforementioned nano black phosphorus heavy oil viscosity reducer in heavy oil viscosity reduction.

[0028] A fourth aspect of the present invention provides a method for reducing the viscosity of heavy oil, comprising mixing heavy oil with the aforementioned nano black phosphorus heavy oil viscosity reducer; preferably, the amount of the nano black phosphorus heavy oil viscosity reducer is 300 to 800 ppm based on the total weight of the mixed raw materials.

[0029] For heavy oil with high asphaltene content, its viscosity is mainly due to the high asphaltene content. The association between asphaltene and colloid components causes the aggregation of molecules of heavy components of heavy oil, thereby increasing the viscosity of heavy oil. In addition, in addition to the high content of hydrocarbon elements in heavy oil, metal elements such as nickel and vanadium also appear in large quantities in heavy oil. These metal elements, as physical crosslinking points, will strengthen the interaction between asphaltene and colloid, increase the difficulty of reducing the viscosity of heavy oil, and thus put forward high requirements for heavy oil mining and processing technology. The present invention combines black phosphorus nanosheets and molybdenum disulfide nanosheets modified by oil-soluble polymers, on the one hand, can disperse the dispersion before the heavy component; on the other hand, it can destroy the physical crosslinking points between asphalt and colloid, further reducing the viscosity of heavy oil. Specifically, the existing improvements on oil-soluble viscosity reducers focus on increasing the polar functional groups of oil-soluble polymers, thereby increasing the interaction between oil-soluble polymers and asphaltene. These polar groups are mostly amino, carboxyl, etc. However, the interaction between the polar functional groups and asphaltene is weak, and the interaction can only be enhanced by increasing the number of polar functional groups. Different from the prior art, the present invention introduces black phosphorus nanosheets as a strong polar group, which has high activity, strong interaction force, good temperature and salt resistance. It can not only destroy the cross-linking points between asphaltene and colloid, but also greatly increase the interaction force between the viscosity reducer and the heavy components, and can efficiently disperse the asphalt colloid to achieve the purpose of reducing the viscosity of heavy oil.

[0030] The beneficial effects of the present invention are:

[0031] The raw materials for preparing the nano black phosphorus heavy oil viscosity reducer of the present invention include oil-soluble polymer-modified molybdenum disulfide nanosheets, black phosphorus nanosheets and a coupling agent, wherein: 1) compared with unmodified molybdenum disulfide nanosheets, the oil-wetting property of the oil-soluble polymer-modified molybdenum disulfide nanosheets is enhanced, and the oil-wetting property can be better dispersed in heavy oil. The molybdenum disulfide nanosheets serve as the core of the oil-soluble polymer, and the modified structure thereof is similar to a comb, with the molybdenum disulfide nanosheets as the comb back and the polymer as the comb teeth. The structure is conducive to the stretching of the polymer and the stretching of the polar functional groups. Compared with the polymer form of random coils in the prior art, the structure has a stronger interaction force with asphaltene and colloid. Since the polymer is grafted copolymerized on the surface of the molybdenum disulfide nanosheets, the temperature resistance and salt resistance of the overall structure are further improved, and the adaptability to the oil reservoir is enhanced. 2) There is a supramolecular interaction between black phosphorus nanosheets and metal ions, which will adsorb metal ions in heavy oil on the surface, passivate the lone pair of electrons of phosphorus atoms in black phosphorus, greatly improve the stability of black phosphorus sheets, and destroy the crosslinking points between asphalt and colloid, reducing the viscosity of crude oil. 3) The coupling agent plays the role of connecting the oil-soluble polymer modified molybdenum disulfide nanosheets and black phosphorus nanosheets. When the coupling agent adopts a silane coupling agent, the silicon oxygen bond in the silane coupling agent will be connected to the surface of the molybdenum disulfide nanosheet, and the amino group in the silane coupling agent is connected to the surface of the black phosphorus, so that the two nanosheets are combined together by covalent bonds, and then interact with heavy oil as a whole. The stability is stronger than the general van der Waals force bonding mode, and it is not easy to separate the chromatographic column during the flow of the reservoir. The present invention can prepare a heavy oil viscosity reducer with a viscosity reduction rate of up to 93.64%, good temperature and salt resistance, good compatibility with crude oil, and not easy to aggregate by compounding the above raw materials and carrying out a suitable weight ratio. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Unless otherwise specified, the raw materials and reagents in the following examples are all commercially available products, and all are analytically pure.

[0034] Example 1

[0035] This embodiment provides a nano black phosphorus heavy oil viscosity reducer, and the preparation method is as follows:

[0036] (1) 1g 1T crystalline molybdenum disulfide powder (100nm) was ultrasonically dispersed in 30mL water, the ultrasonic frequency was 40KHZ, and the ultrasonic time was 20min; 80.2g 20-ethyl methacrylate, 13.61g styrene, 6.19g acrylamide, 9.9g OP-10 and 6.6g Tween 60 were added to 300mL toluene. Then 30mL of molybdenum disulfide aqueous solution was slowly dripped into the toluene solution and stirred to form a uniform and stable emulsion; after nitrogen was introduced, 1g azobisisobutyronitrile was added to the emulsion and reacted at 90°C for 5h. After the reaction was completed, the product was washed with methanol to obtain a single-side oil-soluble polymer modified molybdenum disulfide nanosheet;

[0037] (2) 1 g of molybdenum disulfide nanosheets modified with a single-side oil-soluble polymer, 2 g of black phosphorus nanosheets (50 nm) and 3 g of γ-aminopropyltriethoxysilane were dissolved in 100 mL of toluene and stirred at 50 °C for 8 h. After the reaction, the product was washed with methanol and dried at 80 °C to obtain a nano black phosphorus heavy oil viscosity reducer.

[0038] Example 2

[0039] This embodiment provides a nano black phosphorus heavy oil viscosity reducer, and the preparation method is as follows:

[0040] (1) 1g 1T crystalline molybdenum disulfide powder (200nm) was ultrasonically dispersed in 30mL water, the ultrasonic frequency was 40KHZ, and the ultrasonic time was 30min; 316.49g dodecyl methacrylate, 49.94g styrene, 33.57g acrylamide, 10g OP-10 and 20g Span 60 were added to 470mL toluene. Then 30mL of molybdenum disulfide aqueous solution was slowly dripped into the toluene solution and stirred to form a uniform and stable emulsion; after nitrogen was introduced, 3.2g azobisisobutyronitrile was added to the emulsion, and the reaction was carried out at 90°C for 8h. After the reaction was completed, the product was washed with methanol to obtain a single-side oil-soluble polymer modified molybdenum disulfide nanosheet;

[0041] (2) 5 g of molybdenum disulfide nanosheets modified with a single-side oil-soluble polymer, 10 g of black phosphorus nanosheets (80 nm) and 25 g of γ-aminopropyltrimethoxysilane were dissolved in 300 mL of toluene and stirred at 30 °C for 12 h. After the reaction was completed, the product was washed with methanol and dried at 80 °C to obtain a nano black phosphorus heavy oil viscosity reducer.

[0042] Example 3

[0043] This embodiment provides a nano black phosphorus heavy oil viscosity reducer, and the preparation method is as follows:

[0044] (1) 0.5 g of 1T crystalline molybdenum disulfide powder (150 nm) was ultrasonically dispersed in 20 mL of water at an ultrasonic frequency of 40 KHZ and an ultrasonic time of 20 min; 82.33 g of tetradecyl methacrylate, 17.67 g of divinylbenzene, 9 g of OP-10 and 9 g of Span 40 were added to 280 mL of toluene. Then 20 mL of molybdenum disulfide aqueous solution was slowly dripped into the toluene solution and stirred to form a uniform and stable emulsion; after nitrogen was introduced, 0.8 g of azobisisobutyronitrile was added to the emulsion and reacted at 90 ° C for 8 h. After the reaction was completed, the product was washed with methanol to obtain a single-side oil-soluble polymer modified molybdenum disulfide nanosheet;

[0045] (2) 1 g of molybdenum disulfide nanosheets modified with a single-side oil-soluble polymer, 2 g of black phosphorus nanosheets (50 nm) and 2 g of γ-aminopropyltrimethoxysilane were dissolved in 100 mL of toluene and stirred at 40 °C for 10 h. After the reaction, the product was washed with methanol and dried at 80 °C to obtain a nano black phosphorus heavy oil viscosity reducer.

[0046] Example 4

[0047] This embodiment provides a nano black phosphorus heavy oil viscosity reducer, and the preparation method is as follows:

[0048] (1) 1g 1T crystalline molybdenum disulfide powder (100nm) was ultrasonically dispersed in 20mL water, the ultrasonic frequency was 40KHZ, and the ultrasonic time was 30min; 42.02g 20-ethyl methacrylate, 48.39g 24-ethyl methacrylate, 7.14g styrene, 2.45g acrylamide, 9g OP-10 and 9g Span 40 were added to 280mL toluene. Then 20mL of molybdenum disulfide aqueous solution was slowly dripped into the toluene solution and stirred to form a uniform and stable emulsion; after nitrogen was introduced, 0.6g azobisisobutyronitrile was added to the emulsion, and the reaction was carried out at 60°C for 8h. After the reaction was completed, the product was washed with methanol to obtain a single-side oil-soluble polymer modified molybdenum disulfide nanosheet;

[0049] (2) 1 g of molybdenum disulfide nanosheets modified with a single-side oil-soluble polymer, 2 g of black phosphorus nanosheets (50 nm) and 6 g of N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane were dissolved in 100 mL of toluene and stirred at 40 °C for 6 h. After the reaction, the product was washed with methanol and dried at 80 °C to obtain a nano black phosphorus heavy oil viscosity reducer.

[0050] Comparative Example 1

[0051] (1) 80.2 g of eicosyl methacrylate, 13.61 g of styrene and 6.19 g of acrylamide were added to 300 mL of toluene. After nitrogen was introduced, 1 g of azobisisobutyronitrile was added and reacted at 90° C. for 5 h. After the reaction was completed, the product was washed with methanol to obtain an oil-soluble heavy oil viscosity reducer;

[0052] (2) 1 g of oil-soluble heavy oil viscosity reducer, 2 g of black phosphorus nanosheets (50 nm) and 3 g of γ-aminopropyltriethoxysilane were dissolved in 100 mL of toluene and stirred at 50 °C for 8 h. After the reaction was completed, the product was washed with methanol and dried at 80 °C to obtain a nano black phosphorus heavy oil viscosity reducer.

[0053] Comparative Example 2

[0054] (1) 1g 1T crystalline molybdenum disulfide powder (100nm) was ultrasonically dispersed in 30mL water, the ultrasonic frequency was 40KHZ, and the ultrasonic time was 20min; 80.2g 20-ethyl methacrylate, 13.61g styrene, 6.19g acrylamide, 9.9g OP-10 and 6.6g Tween 60 were added to 300mL toluene. Then 30mL of molybdenum disulfide aqueous solution was slowly dripped into the toluene solution and stirred to form a uniform and stable emulsion; after nitrogen was introduced, 1g azobisisobutyronitrile was added to the emulsion and reacted at 90°C for 5h. After the reaction was completed, the product was washed with methanol to obtain a single-side oil-soluble polymer modified molybdenum disulfide nanosheet;

[0055] (2) 1 g of molybdenum disulfide nanosheets modified with a single-side oil-soluble polymer and 3 g of γ-aminopropyltriethoxysilane were dissolved in 100 mL of toluene and stirred at 50 °C for 8 h. After the reaction, the product was washed with methanol and dried at 80 °C to obtain a nano black phosphorus heavy oil viscosity reducer.

[0056] Experimental example

[0057] This experimental example evaluates the viscosity reduction rate of the nano black phosphorus heavy oil viscosity reducer obtained in Examples 1 to 4 and Comparative Examples 1 to 2, including the following steps:

[0058] (1) Determination of heavy oil viscosity. Before measurement, the heavy oil samples must be uniformly preheated at 80°C and stirred continuously for 1 hour before cooling to 50°C. The viscosity of the heavy oil is measured using a digital viscometer to eliminate experimental errors caused by local inhomogeneity of the heavy oil or differences in physical properties.

[0059] (2) Evaluation of viscosity reduction rate. Take a certain amount of heavy oil at room temperature and heat it to 50°C. In order to better disperse the oil-soluble viscosity reducer into the heavy oil, dissolve the viscosity reducer in 3 mL of toluene, then add it to 100 mL of heavy oil, stir it with a glass rod every 20 minutes and keep the temperature constant for 2 hours to allow the heavy oil and the viscosity reducer to fully react. Use a digital viscometer to measure the viscosity of the heavy oil after adding the viscosity reducer, and calculate the viscosity reduction rate according to the formula:

[0060]

[0061] Where W is the viscosity reduction rate of heavy oil, %; η0 is the original viscosity of heavy oil, mPa·s; η is the viscosity of heavy oil after adding viscosity reducer, mPa·s.

[0062] The experimental results are shown in the following table:

[0063] Table 1

[0064] Group Viscosity reduction rate / % Example 1 90.64 Example 2 88.34 Example 3 85.33 Example 4 93.64 Comparative Example 1 62.31 Comparative Example 2 75.97

[0065] As can be seen from Table 1, the viscosity reduction rate of the nano black phosphorus viscous oil viscosity reducer of the present invention is relatively high, generally above 85%. With the increase of the types of polymer monomers, the viscosity reduction rate effect of the nano black phosphorus viscous oil viscosity reducer is further improved. The polymer in Example 4 is a quaternary copolymer, and the effect is the best, which can reach 93%. Comparative Example 1 does not add molybdenum disulfide nanosheets, and the obtained viscosity reducer is black phosphorus dispersed in an oil-soluble viscosity reducer. Black phosphorus itself is hydrophilic, and has poor dispersion effect in crude oil and oil-soluble polymers, and is easy to aggregate into agglomerates, so the viscosity reduction effect is poor. Comparative Example 2 does not add black phosphorus nanomaterials, and only the molybdenum disulfide nanosheets modified by a unilateral oil-soluble polymer work. Due to the weak interaction between the polar functional group and asphaltene, its viscosity reduction effect is also worse than that of the nano black phosphorus viscous oil viscosity reducer.

[0066] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A nano black phosphorus heavy oil viscosity reducer, characterized in that: The preparation raw materials include: oil-soluble polymer modified molybdenum disulfide nanosheets, black phosphorus nanosheets and a coupling agent, wherein the mass ratio of the oil-soluble polymer modified molybdenum disulfide nanosheets, black phosphorus nanosheets and the coupling agent is 1:2:2-6.

2. The nano black phosphorus thick oil viscosity reducer according to claim 1, characterized in that: The oil-soluble polymer-modified molybdenum disulfide nanosheets have a continuous phase containing an oil-soluble polymer and a dispersed phase containing molybdenum disulfide nanosheets dispersed in the continuous phase.

3. The nano black phosphorus thick oil viscosity reducer according to claim 2, characterized in that: The polymer monomer of the oil-soluble polymer forming the continuous phase is selected from one or a combination of two or more of acrylamide, styrene, divinylbenzene, eicosyl methacrylate, docosyl methacrylate, and tetracosyl methacrylate; Preferably, the polymer monomers of the oil-soluble polymer forming the continuous phase are a combination of acrylamide, styrene, eicosyl methacrylate and tetracosyl methacrylate; more preferably, the mass ratio of acrylamide, styrene, eicosyl methacrylate and tetracosyl methacrylate is 2-3:7-8:42-43:48-49.

4. The nano black phosphorus thick oil viscosity reducer according to claim 2, characterized in that: The molybdenum disulfide nanosheets forming the dispersed phase are selected from molybdenum disulfide nanosheets with a 1T crystal form, and the size of the molybdenum disulfide nanosheets is 100-200 nm.

5. The nano black phosphorus heavy oil viscosity reducer according to any one of claims 1 to 4, characterized in that: The preparation method of the oil-soluble polymer modified molybdenum disulfide nanosheets comprises: S1. Preparation of aqueous phase: mixing molybdenum disulfide powder with water and then performing ultrasonic exfoliation to obtain an aqueous phase; S2, oil phase preparation: polymer monomers, oil-soluble emulsifiers, and oily solvents are mixed to obtain an oil phase; S3, emulsification: adding the water phase to the oil phase and stirring to form a uniform and stable emulsion; S4, polymerization: under an inert atmosphere, add an initiator to the emulsion and heat to react; Preferably, the ultrasonic time is 20 to 30 minutes, and the ultrasonic frequency is 40KHZ; Preferably, the mass ratio of the molybdenum disulfide powder to the polymer monomer is 1:100-400; Preferably, the oil-soluble emulsifier is selected from one or a combination of two or more of dodecylphenol polyoxyethylene ether, sorbitan monostearate, sorbitan monopalmitate, and polysorbate 60; preferably, the amount of the oil-soluble emulsifier is 5 to 10% of the total volume of the emulsion raw material; Preferably, the oily solvent comprises toluene; Preferably, the initiator comprises azobisisobutyronitrile; preferably, the amount of the initiator is 0.6 to 1% of the mass of the polymer monomer; Preferably, the reaction temperature is 50-90° C., and the reaction time is 4-8 hours.

6. The nano black phosphorus heavy oil viscosity reducer according to claim 1, characterized in that: The size of the black phosphorus nanosheet is 50-100 nm.

7. The nano black phosphorus heavy oil viscosity reducer according to claim 1, characterized in that: The coupling agent is a silane coupling agent, and the silane coupling agent is selected from any one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane.

8. A method for preparing the nano black phosphorus heavy oil viscosity reducer according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Molybdenum disulfide nanosheets modified by an oil-soluble polymer, black phosphorus nanosheets, a coupling agent and an oily solvent are mixed and stirred to react; Preferably, the oily solvent comprises toluene; Preferably, the reaction temperature is 30-50°C and the reaction time is 8-12h; Preferably, the method further comprises washing and drying the reaction product.

9. Use of the nano black phosphorus heavy oil viscosity reducer according to any one of claims 1 to 7 in heavy oil viscosity reduction.

10. A method for reducing the viscosity of heavy oil, characterized in that: The method comprises mixing heavy oil and the nano black phosphorus heavy oil viscosity reducer according to any one of claims 1 to 7; preferably, the dosage of the nano black phosphorus heavy oil viscosity reducer is 300 to 800 ppm based on the total weight of the mixed raw materials.

Citation Information

Patent Citations

  • Nano SiO2 composite material thickened oil viscosity reducer and preparation method thereof

    CN104327225A

  • Magnetic-based black phosphorus nano oil-displacing agent and preparation method thereof

    CN112210356A

  • Magnetic nano oil-displacing agent taking black phosphorus as matrix and preparation method of magnetic nano oil-displacing agent

    CN112251206A

  • Hyperbranched modified nano material, preparation method thereof and application of hyperbranched modified nano material in thick oil viscosity reducer

    CN113881052A

  • Viscoelastic-active nano viscosity reducer as well as preparation method and application thereof

    CN115029123A